A49 CO-INFECTION WITH PARASITIC WORMS ENHANCES THE ABILITY OF SALMONELLA TO COLONIZE THE GUT LUMEN AND DEWORMING RESTORES COLONIZATION RESISTANCE TO SALMONELLA. (26th February 2020) - Brosschot, T P; Lawrence, K M; Kennedy, M H; FitzPatrick, R D; Moeller, B E; Han, J; Borchers, C; Reynolds, L A
Abstract: Background: Chronic infections with intestinal helminths occur primarily in world regions where infections with bacterial pathogens are also common. Research so far has shown that helminths can promote bacterial infection, however, the precise mechanisms of this are unknown. Current helminth control strategies involve mass deworming programs, and it is as yet unclear how deworming impacts susceptibility to bacterial infections in helminth-affected areas. Aims: Our aims were to decipher the mechanistic details by which helminths can promote intestinal bacterial infection, and to determine how deworming affects susceptibility to intestinal colonization by bacterial pathogens. Methods: Using a mouse model of enteric helminth-bacterial coinfection, we examined how the small intestinal helminth Heligmosomoides polygyrus promotes intestinal colonization by Salmonella enterica serovar Typhimurim. To study the effect of deworming of concurrent Salmonella infection, we treated our helminth-infected mice with the anthelmintic drug Strongid P both before and after Salmonella (co-) infection. To examine whether heightened Salmonella colonization during helminth infection depended on the ability of Salmonella to invade host tissue, we compared the ability of wild-type Salmonella or an invasion-deficient mutant (Δ invA ) to colonize during helminth co-infection. Results: An ongoing helminth infection resulted in high levels of Salmonella in the small intestine after co-infection, however, when mice were dewormed prior to Salmonella co-infection, they were no longer susceptible to high small intestinal Salmonella burdens. In contrast, when helminth-infected mice are dewormed after Salmonella has already co-colonized, high Salmonella burdens persisted in the small intestine. Further, we found that during helminth co-infection, Salmonella primarily expands in the gut lumen rather than in the small intestinal tissue, and in line with this, a Salmonella invasion mutant was able to colonize the intestine to a similar extent to wild-type Salmonella during helminth infection. Conclusions: Deworming experiments have revealed that the effects of H. polygyrus on promoting Salmonella colonization in the small intestines depend on the ongoing presence of the helminth. Deworming did not revert bacterial burdens once Salmonella had colonized, suggesting that an ongoing helminth infection reduces colonization resistance to Salmonella infection but was not required for Salmonella to persist after initial colonization by Salmonella . Further, we discovered that Salmonella expansion during helminth infection is independent of bacterial invasion of host tissue. Funding Agencies: CIHR